Microbiological and Physicochemical Characteristics of Inasua Traditional Fish Fermented from Maluku Islands - Ferymon Mahulette; Nisa Rachmania Mubarik; Antonius Suwanto; Widanarni Widanarni (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2018)
Based on the raw materials, inasua consists of two types namely inasua with sap and inasua without sap. Research of inasua with sap has never been done and considered as the novelty of this research. The sensory characteristics and shelf life of two types of inasua were different. The research aims to analyze the microbiological and physicochemical characteristics of two types of inasua during fermentation. The microbiological analyzes include the total number of bacteria and lactic acid bacteria, while physicochemical analyzes include temperature, pH, water activity, proximate analysis, salt, alcohol, histamine, amino acids and fatty acids contents. The total number of bacteria and lactic acid bacteria has decreased during fermentation. At the end of the fermentation the total number of bacteria and lactic acid bacteria inasua with sap were 3.2x107 CFU/g and 3.0x107 CFU/g, while inasua without sap were 5.4x105CFU/g and 3.5x105 CFU/g, respectively. The moisture, protein, alcohol contents and water activity decreased, otherwise the salt, fat, ash, amino acids, and fatty acids contents increased during fermentation. Generally, microbiological and physicochemical characteristics of inasua with sap was better than inasua without sap. The results of this research to improve the quality of this fermentation product in the future.